Acquired hemophilia A and plasma cell neoplasms: a case report and review of the literature - Jalowiec, Katarzyna A. (J Med Case Rep, 2020)
BACKGROUND: Acquired hemophilia A is a rare autoimmune disease with clinically often significant bleeding diathesis resulting from circulating autoantibodies inhibiting coagulation factor VIII. Half of acquired hemophilia A cases are associated with an underlying disorder, such as autoimmune diseases, cancer, or use of certain drugs, or occur during pregnancy and in the postpartum period. In the other half, no underlying cause is identified. An association of acquired hemophilia A with plasma cell neoplasm seems to be extremely rare. CASE PRESENTATION: We describe a case of a 77-year-old Swiss Caucasian man who was diagnosed with acquired hemophilia A and smoldering multiple myeloma as an underlying cause. Acquired hemophilia A was treated with prednisolone, cyclophosphamide, and immunoadsorption. Extensive workup revealed a plasma cell neoplasm as the only disorder associated with or underlying the acquired hemophilia A. For long-term control of acquired hemophilia A, we considered treatment of the plasma cell neoplasm necessary, and a VRD (bortezomib, lenalidomide, and dexamethasone) regimen was initiated. Due to multiple complications, VRD was reduced to VRD-lite after two cycles. After nine cycles of induction therapy and five cycles of consolidation therapy, the patient is in complete remission of his acquired hemophilia A and very good partial remission of the plasma cell neoplasm. We conducted a literature review to identify additional cases of this rare association and identified 15 other cases. Case descriptions, including the sequence of occurrence of acquired hemophilia A and plasma cell neoplasm , treatment, evolution, and outcome are presented. DISCUSSION AND CONCLUSIONS: Our case, together with 15 other cases described in the literature, underscore the possibility of plasma cell neoplasm as an underlying cause of acquired hemophilia A. Physicians should consider including protein electrophoresis, immunofixation, and analysis of free light chains in laboratory diagnostics when treating a patient with acquired hemophilia A. The occurrence of excessive and unexplained bleeding in patients diagnosed with plasma cell neoplasm should raise suspicion of secondary acquired hemophilia A and trigger the request for coagulation tests, particularly in patients treated with immunomodulatory drugs such as thalidomide or lenalidomide. Additionally, early intervention with immunoadsorption can be lifesaving in cases with high-titer factor VIII inhibitors, especially when surgical interventions are necessary.